Evidence that Evidence Doesn't Matter: The Case of Human Trafficking in Canada - Roots, Katrin; De Shalit, Ann (Atlantis, 2015)
This article considers the ways in which the political pressures that have structured Canada’s involvement in the fight against human trafficking and the on-the-ground enforcement of laws adopted through Canada’s positioning as an anti-trafficking nation have created a problem that necessitates regulation. Although the problem could be interpreted as a legal fiction, its effects are real and include greater restrictions on migrants, a lack of attention to wide-ranging labour abuses, and the tightening of the net around sex work.